Best Answer

That doesn't need factoring, it needs solving.

2x = 1

x = 1/2

Q: How do you factor this x plus x equals 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-((4x + 1)(x - 1))

(x + 3)(x + 2)

(3x + 1)(4x - 1)(x - 2)

1

(2x-4)(x-1) = 0

Related questions

-((4x + 1)(x - 1))

4(x + 1) = 0.

x3+x2+x First, factor out the x: x(x2+x+1) Could stop there, but the rest is factor-able using imaginary numbers: x(x+.5(1+i(3).5)(x+.5(1-i(3).5), where i = (-1).5, or sqrt(-1)

That equals 1.25x. There's nothing to factor.

3(2x - 1)(x - 2)

(x + 3)(x + 2)

(3x + 1)(4x - 1)(x - 2)

(x + 3)(x + 4)

It is: (5x-1)(x-1) = 0 Therefore: x = 1/5 or x = 1 Use the quadratic equation formula

1

(2x-4)(x-1) = 0

0 because X= -1